Torchbearer of freedom : the influence of Richard Price on eighteenth century thought - Cone, Carl B. (University of Kentucky Press, 1952)
A bronze inscription in the public library of Bridgend calls Richard Price ""Philosopher. Preacher. Actuary. Cfaill Dynolryw"" [Friend of Humanity]. He was all these and something more. Son of a Welsh Presbyterian of Calvinistic leaning, Richard Price was educated for the ministry. That he belonged in the best of Dissenting tradition was exhibited at an early age in his own interest in Arianism, an interest fostered by the academy at Pentwyn where he studied. Here he met the works of Samuel Clarke, which thoroughly aroused the ire of his father. Richard Price did not cringe in the face of hosti.